1997
DOI: 10.1113/expphysiol.1997.sp004065
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 8h of eucapnic and poikilocapnic hypoxia on middle cerebral artery velocity and heart rate in humans

Abstract: SUMMARYThis study examines the effects of prolonged hypoxia, with and without control of end-tidal CO2 partial pressure (PET,CO2), on the intensity-weighted mean velocity of blood flow in the middle cerebral artery (VIwM) and on heart rate (HR). Specifically, the time course of the responses, their reversibility with brief periods of hyperoxia and the recovery phase following prolonged hypoxia were all investigated. Twelve subjects were studied, of whom nine provided satisfactory data. A purpose-built chamber … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
1
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 21 publications
3
1
0
Order By: Relevance
“…Our control data showed an increase in heart rate over the 8 h of hypoxia. This is consistent with previous results in humans from our laboratory (Clar et al 1997b;Dorrington et al 1997) and with results from other laboratories in humans (Grover et al 1976;Hoon et al 1977) and sheep (Krasney et al 1984(Krasney et al , 1985. It is important to note the period over which this…”
Section: Effects On Heart Rate -Comparison With Other Studies In Humanssupporting
confidence: 93%
See 2 more Smart Citations
“…Our control data showed an increase in heart rate over the 8 h of hypoxia. This is consistent with previous results in humans from our laboratory (Clar et al 1997b;Dorrington et al 1997) and with results from other laboratories in humans (Grover et al 1976;Hoon et al 1977) and sheep (Krasney et al 1984(Krasney et al , 1985. It is important to note the period over which this…”
Section: Effects On Heart Rate -Comparison With Other Studies In Humanssupporting
confidence: 93%
“…Consistent with our previous results (Clar et al 1997b), most of the observed increase in heart rate appears to be linked to an increase in G HR , with only a small, barely detectable effect on heart rate during acute hyperoxia. We are unaware of any other studies examining the heart rate response to prolonged hypoxia during muscarinic blockade.…”
Section: Figuresupporting
confidence: 92%
See 1 more Smart Citation
“…A possible explanation for this difference is that the subjects were exposed to a greater degree of hypoxia in the previous studies compared with the present one. Two studies of isocapnic hypoxia of shorter duration (up to 8 h) in humans failed to find any evidence of adaptation of the CBF over the time course of the exposure (Jensen et al 1992;Clar et al 1997), which is a result in keeping with the present study.…”
Section: Hypoxic Exposure and Comparisons With Previous Studies Of Cbfsupporting
confidence: 88%